VALOR NUTRITIVO, COMPORTAMENTO INGESTIVO E DESEMPENHO DE BOVINOS SUPLEMENTADOS COM FARELO DE BABAÇU EM SISTEMAS SILVIPASTORIS NA REGIÃO PRÉ-AMAZÔNICA - TOSTA, Xerxes Moraes (2014)
The objective of the present study was to evaluate the structure of the pasture, feeding behavior and performance of growing cattle supplemented with babassu meal and kept in silvopastoral systems composed of babassu and Marandu grass. The experiment was conducted at Farm Água Viva, in the municipality of Matinha-MA, from November 2012 to January 2013 27 crossbred steers (Nelore x Guzerat) were used, whole, with an average age of 24 months and average weight of 219.2 kg in silvopastoral systems composed of different densities of the babassu palm and Marandu grass. The treatments were: three densities of babassu palm: 39, 72 and 92 palms per hectare, respectively, and three increasing levels of babassu meal which corresponded to 10, 20 and 30% in a 3x3 factorial arrangement, respectively, with three replicates in a completely randomized design. Forage production in pastoral environments was not affected by the thickness of palm, however levels of babassu meal in the proportions 10 and 20% resulted in greater accumulation of dead material in the pasture and also interfered with the leaf/stem ratio. The supply of supplementation with increasing levels of babassu meal modified the feeding behavior of cattle grazing. Supplementation with 20% babassu meal in pastures with 72 palm/ha trees reduces grazing time, increases idle time and displacement. Densities of palm trees in pastures and use of increasing levels of babassu meal in the diet did not affect weight gain of growing cattle.